2022
DOI: 10.1021/acs.jafc.2c00551
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Microbial Metabolism of (+)-Catechin Reveals Fast and Slow Converters with Individual-Specific Microbial and Metabolite Markers

Abstract: The bioavailability of catechin highly relies on gut microbiota which may determine its metabolic profile, resulting in different health outcomes. Here, we investigated in vitro (+)-catechin metabolism by human microbial communities. There were substantial interindividual differences in the metabolic profiles of (+)-catechin, with 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone being the major contributor. Furthermore, the microbial metabolic rate of catechin enabled stratification of 12 participants (fast, medium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 51 publications
3
38
2
Order By: Relevance
“…Subsequently, diphenylpropan-2-ol is converted into its A-ring fission metabolites, 3,4-diHPV and 4-hydroxy-5-(3′,4′-dihydroxyphenyl)-valeric acid (4H-diHPVA), and this step is reported to be mediated by Flavonifractor plautii ( 44 ). Differences in the time-dependent formation of 3,4-diHPV were also reported in a recently published study by Li et al ( 45 ). They studied in vitro microbial metabolism of (+)-catechin, and the major metabolite 3,4-diHPV was also found to peak at different time points in different individuals, e.g., 24 h for individual 1, 48 h for individual 6, and 72 h for individual 7.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Subsequently, diphenylpropan-2-ol is converted into its A-ring fission metabolites, 3,4-diHPV and 4-hydroxy-5-(3′,4′-dihydroxyphenyl)-valeric acid (4H-diHPVA), and this step is reported to be mediated by Flavonifractor plautii ( 44 ). Differences in the time-dependent formation of 3,4-diHPV were also reported in a recently published study by Li et al ( 45 ). They studied in vitro microbial metabolism of (+)-catechin, and the major metabolite 3,4-diHPV was also found to peak at different time points in different individuals, e.g., 24 h for individual 1, 48 h for individual 6, and 72 h for individual 7.…”
Section: Discussionsupporting
confidence: 75%
“…The formation of 3,4-diHPV from EC, which includes several reaction steps and reflects a balance between its formation and subsequent further conversion, showed larger inter-and intra-individual differences, than the decrease of EC, suggesting the reactions require specific groups of microbiotas. So far, Lactobacillus plantarum, Eggerthella lenta, Adlercreutzia equolifaciens, and Eubacterium SDG-2 are the only identified microbiota that can open the C-ring of catechins to form diphenylpropan-2-ol, the precursor of 3,4-diHPV (42)(43)(44)(45). Subsequently, diphenylpropan-2-ol is converted into its A-ring fission metabolites, 3,4-diHPV and 4-hydroxy-5-(3 ′ ,4 ′ -dihydroxyphenyl)-valeric acid (4H-diHPVA), and this step is reported to be mediated by Flavonifractor plautii (44).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies performed on fecal slurries from healthy volunteers supplemented with 200 mg/L of (+)catechins, to mimic the mean daily intake due to green tea drinking, has confirmed the high interindividual variability in the production of EGCG metabolites with the possibility to stratify subjects in low, medium and high metabolizers [88]. Interestingly, fast converters show higher microbiota variability and diversity in taxa composition, a sign of a healthy microbial environment…”
Section: Epigallocatechin-3-gallatementioning
confidence: 83%
“…Ma et al (2019) found that certain flavanols (e.g., catechin) can have antimicrobial activity against pathogenic bacteria such as E. coli and Clostridium [ 61 ]. These findings can be attributed to increased SCFA production associated with catechin metabolism by microorganisms within the intestine [ 62 , 63 , 64 ]. Further, dietary supplementation with catechins and similar compounds could have promoted the expression of serum leptin and induced carbohydrate degradation, which may regulate the presence and abundance of certain bacterial strains [ 65 ].…”
Section: Discussionmentioning
confidence: 99%